SELF REGULATED LEARNING SISWA SMP DALAM PEMECAHAN MASALAH MATEMATIS - Rama Nida Siregar; Sufyani Prabawanto; Didi Suryadi (Journal on Mathematics Education Research (J-MER), 2021)
This study aims to describe the self-regulated learning of junior high school students in Medan City and Deli Serdang Regency, North Sumatra in solving mathematical problems in social arithmetic material. This research includes survey research with quantitative and qualitative approaches. The research subjects were 65 junior high school students in Medan City and Deli Serdang Regency, North Sumatra who came from two schools with the category of one public school and one private school. The instrument used is a self-regulated learning questionnaire consisting of 27 statement items based on self-regulated learning indicators to be filled out by students, and interview guidelines. The results showed that the average self-study of private junior high schools in Medan City and Deli Serdang Regency, North Sumatra as a whole of 65 students was in the high category, which was 90.23. In general, students have a high tendency to self-study. For example having 1) think far ahead. Students plan behavioral independence by analyzing tasks and setting goals, 2) doing and controlling. Students monitor and control and control their own behavior, awareness, motivation and emotions, 3) Self-reflection. Students state about their own progress and change it according to their behavior, so it can be said that students who have independent learning abilities will have an impact on their learning and students' problem solving will be better